2020
DOI: 10.21203/rs.3.rs-122134/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reliability of A Dried Urine Test for Comprehensive Assessment of Urine Hormones and Metabolites

Abstract: BackgroundMass spectrometry allows for analysis of multiple hormone and organic acid metabolites from small urine volumes; however, to assess the full extent of daily hormone production, 24-hour urine collections are usually required. The aims of this study were, first, to confirm that mass spectrometric analysis of an array of hormones and organic acids would yield similar results in both liquid and dried urine, and, second, to determine if collection of four dried spot urine samples could be substituted for … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…As a primary goal, we have also demonstrated that bottom culture is feasible and the number of colonies formed is comparable to that of a standard top streak. Recently, many tests have been based on analysing dried urine samples, where the samples can be transported on a lter card (16). One of our future aims is to study the e cacy of this system with dried urine samples on a lter card.…”
Section: Discussionmentioning
confidence: 99%
“…As a primary goal, we have also demonstrated that bottom culture is feasible and the number of colonies formed is comparable to that of a standard top streak. Recently, many tests have been based on analysing dried urine samples, where the samples can be transported on a lter card (16). One of our future aims is to study the e cacy of this system with dried urine samples on a lter card.…”
Section: Discussionmentioning
confidence: 99%